Psychological readiness for return to sport following distal femoral osteotomy in patients with recurrent patellar instability - Maximilian Hinz; Peter Rab; Moritz Brunner; Marco-Christopher Rupp; Armin Runer; Luca Grüning; Lisa Rahn; Sebastian Siebenlist; Andrea Achtnich (BMC Musculoskeletal Disorders)
Abstract Background There exists a paucity of data on the relationship between psychological factors and return to sport in patients who undergo surgery for complex patellofemoral instability (PFI). The purpose of this study was to investigate the influence of psychological factors on the return to the preoperative level of sports and knee function in patients with complex PFI who were treated with distal femoral osteotomy (DFO). Methods Patients who underwent DFO for recurrent PFI associated with increased femoral antetorsion and/or valgus malalignment were included. Psychological readiness to resume sporting activities was assessed at a minimum of 12 months postoperatively using the PFI-Return to Sport after Injury (PFI-RSI) scale. A receiver operating curve (ROC) analysis was performed for the PFI-RSI scale and its ability to discriminate between patients who returned to the preoperative level of sport and those who did not. Spearman’s rank-order correlation was used to test for correlations between the PFI-RSI scale and patient-reported outcome measures (PROM), including Banff Patella Instability Instrument 2.0 (BPII 2.0), Kujala score, Tegner Activity Scale (TAS) and Visual Analog Scale (VAS) for pain. Results Sixty-five patients (70.8% female) were included at a median of 61.0 months (40.0-78.5 months) postoperatively. Patients who returned to their preoperative level of sports scored significantly higher on the PFI-RSI scale than patients who did not (75.8 [64.4–84.2] vs. 40.8 [23.4–60.9], p < 0.001). Reaching a threshold value of 55 on the PFI-RSI scale could predict whether or not patients returned to the preoperative level of sport with a sensitivity of 90.9% and a specificity of 70.6% (area under the curve = 0.834; Youden index = 0.615). The PFI-RSI scale showed moderate to strong correlations with PROM. Conclusion Psychological readiness to resume sporting activities correlated with knee function and was significantly higher in patients who achieved the preoperative level of sport than in patients who did not.